KEBEBASAN HAKIM DALAM PENJATUHAN PUTUSAN PERKARA PIDANA (STUDI TERHADAP ALASAN–ALASAN TIDAK DITERIMANYA TUNTUTAN JAKSA PENUNTUT UMUM) - Nur Furqoni, Farid Yulian; Kuswardani, Kuswardani (UNES Law Review, 2023)
The judge in making a decision must be based on two valid pieces of evidence and the conviction obtained by the judge that the criminal act really happened. Such juridical formulation truly guarantees the freedom of judges, so it seems that judges are not bound by the demands of the public prosecutor. Therefore, this study aims to examine the freedom of judges from the aspect of the reasons why judges do not accept the charges of public prosecutors. This research is a normative research, so the data needed is secondary data in the form of legal documents, journals and references relevant to the research problem. The data is analyzed descriptively based on the principles of substantive criminal law and formal criminal law. The results of the study showed that there was no seriousness of the public prosecutor in conducting the prosecution which was shown by the absence of guarantees to bring the defendant, thus violating the principles of fast, simple and low cost justice. This research provides information to the public that judges are not bound by the demands of the public prosecutor.